Perspectives of practitioners on the green infrastructure in Mukalla City, Yemen - Ahmed Bagazi, Omar Ali; Asmawi, M. Zainora; Mahamod, Lukman Hakim; Ab Rahman, Syakir Amir; Abd Aziz, Abdul Razak (Secholian Publication PLT, 2021)
Green infrastructure (GI) is a new term that aims to accomplish sustainable development. It is a platform to achieve a balance between environmental preservation and urban development and achieve economic, social and environmental benefits. However, many countries are suffering from a lack of investment in GI benefits, especially developing countries. Therefore, this study aims to assess the level of attitude among practitioners through assessing their willingness to invest in GI benefits. A quantitative research approach and the questionnaire were designed, containing 17 main benefits of GI to achieve the aim of this study. The questionnaires were distributed manually to the agencies of planning and designing of urban area in Mukalla city. The total number of completed questionnaires entered into this study was 82—the SPSS program approved for results analysis. Relative important index (RII) was used to rank the items, means (X̄) was used to assess the level of attitude among practitioners. Pearson's Chi-square test (χ2) was used to explore the impact of the demographic factors of practitioners on their attitude. In contrast, multiple linear regression was used to predict the relation between attitude and demographic factors. Firstly, the overall means (X̄) revealed that the GI attitude among practitioners in Mukalla city was positive. Secondly, the cross-tabulation revealed that all-male, old and non-government practitioners having a positive attitude, similarly all highly experienced and postgraduate practitioners also had a positive attitude. Pearson's Chi-square test (χ2) showed that experience has no significant influence on GI's economic, social and environmental benefits. Thirdly, multiple linear regression showed that gender and education of practitioners contribute positively toward increasing the level of attitude among practitioners in Mukalla city.